The 102–103° E geodivider in the modern lithosphere structure of Сentral Asia - Yu. G. Gatinsky; T. V. Prokhorova; D. V. Rundquist (Геодинамика и тектонофизика, 2018)
A quasi-linear zone of noticeable geological and geophysical changes, which coincides approximately with 102–103° E meridians, is termed by the authors as “geodivider”. Active submeridional faults are observed predominantly along the zone and coincide with its strike. Seismicity is most intensive in the central part of this zone, from the Lake Baikal to the Three Rivers Region at the Sino-Myanmar frontier. Transects with deep seismic sections and energy dissipation graphs show most sharply increasing seismic energy amounts and hypocenter depths in the western part of the geodivider which delimits (in the first approximation) the Central Asian and East Asian transitional zones between the North Eurasian, Indian and Pacific lithosphere plates. The transpression tectonic regime dominates west of the geodivider under the influence of the Hindustan Indentor pressure, and the transtension regime prevails east of it due to the Pacific subduction slab submergence and continuation. The regime change coincides with an abrupt increase in the crust thickness – from 35–40 km to 45–70 km – west of the geodivider, as reflected in the geophysical fields and metallogenic characteristics of the crust. The direction of P- and S-waves anisotropy together with the GPS data show decoupling layers of the crust and mantle in the southern part of the geodivider. According to our investigations, the 102–103° E geodivider is a regional geological-geophysical border that may be compared with the Tornquist Line, and, by its scale, with the Uralian and Appalachian fronts and some others large structures.